2016
DOI: 10.1074/jbc.m116.729970
|View full text |Cite
|
Sign up to set email alerts
|

Functional Human α7 Nicotinic Acetylcholine Receptor (nAChR) Generated from Escherichia coli

Abstract: Human Cys-loop receptors are important therapeutic targets. High-resolution structures are essential for rational drug design, but only a few are available due to difficulties in obtaining sufficient quantities of protein suitable for structural studies. Although expression of proteins in E. coli offers advantages of high yield, low cost, and fast turnover, this approach has not been thoroughly explored for full-length human Cys-loop receptors because of the conventional wisdom that E. coli lacks the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
0
13
0
4
Order By: Relevance
“…The lower cost, shorter timeline and versatile strains make E. coli an attractive candidate for protein expression, not only for prokaryotic proteins, but also for eukaryotic membrane proteins. Recently, we have successfully produced full-length wild type human α7nAChR using E. coli and demonstrated that the purified α7nAChR retains functionality and pharmacological properties of native α7nAChR (Tillman et al, 2016). The success with α7nAChR paves a new path for the production of eukaryotic pLGICs using E. coli .…”
Section: Production Of Monodisperse Plgics With High Puritymentioning
confidence: 99%
See 1 more Smart Citation
“…The lower cost, shorter timeline and versatile strains make E. coli an attractive candidate for protein expression, not only for prokaryotic proteins, but also for eukaryotic membrane proteins. Recently, we have successfully produced full-length wild type human α7nAChR using E. coli and demonstrated that the purified α7nAChR retains functionality and pharmacological properties of native α7nAChR (Tillman et al, 2016). The success with α7nAChR paves a new path for the production of eukaryotic pLGICs using E. coli .…”
Section: Production Of Monodisperse Plgics With High Puritymentioning
confidence: 99%
“…Most studies have performed functional measurements in Xenopus oocytes or HEK cells heterologously expressing the pLGIC constructs (Bocquet et al, 2007; Du et al, 2015; Hibbs & Gouaux, 2011; Hilf & Dutzler, 2009; Huang et al, 2015; Miller & Aricescu, 2014; Morales-Perez et al, 2016). The purified pLGIC can also be directly tested for channel function, either directly measuring function of reconstituted pLGICs in the lipid bilayer (Hilf & Dutzler, 2008) or by injecting vesicles containing purified pLGICs into Xenopus oocytes for functional measurements (Labriola et al, 2013; Tillman et al, 2016). …”
Section: Production Of Monodisperse Plgics With High Puritymentioning
confidence: 99%
“…Τα συστήματα αυτά έχουν χρησιμοποιηθεί για την υπερέκφραση περιοχών ή κολοβών κατασκευών άλλων υποδοχέων Cys-θηλιάς ή/και άλλων υπομονάδων του νικοτινικού υποδοχέα. Συγκεκριμένα, το Rosetta 2(DE3) έχει χρησιμοποιηθεί για την έκφραση της ολόκληρης, αγρίου τύπου α7 υπομονάδας του ανθρώπου (Tillman et al 2016, Elberson et al 2017, η P. pastoris για την έκφραση εξωκυττάριων περιοχών άλλων υπομονάδων του νικοτινικού υποδοχέα (Zouridakis et al 2009, Stergiou et al 2011, Kouvatsos et al 2016) και τα κύτταρα Sf9 για την παραγωγή άλλων υποδοχέων Cys-θηλιάς, όπως του GluClαR (Hibbs and Gouaux 2011), του υποδοχέα 5ΗΤ3Α επίμυος (Basak et al 2018), του β3 GABAAR και του α7 nAChR (Radner et al 2012), αλλά και κολοβών μορφών του α4β2 nAChR (Kouvatsos et al 2014).…”
Section: μοριακός σχεδιασμός (Molecular Engineering) του πλαισίου ανάγνωσης για τις μεμβρανικές κατασκευές της α9 υπομονάδαςunclassified
“…Ο α7 ή ο α4β2 nAChR μπορεί να εκφραστεί σε βακτήρια (Tillman et al 2016), κυτταρικές σειρές εντόμων (Radner et al 2012) ή θηλαστικών (Gu et al 2016, Morales-Perez et al 2016a, Matta et al 2017, ενώ κολοβές (truncated) κατασκευές των υπομονάδων τους, στις οποίες έχει αποκοπεί μεγάλο τμήμα της κυτταροπλασματικής τους περιοχής, έχουν βελτιωμένα χαρακτηριστικά έκφρασης σε σχέση με τις ολόκληρες (Kracun et al 2008, Valor et al 2002, Kouvatsos et al 2014, Morales-Perez et al 2016a. Αντίστοιχες μελέτες δεν είχαν γίνει για τους α9*nAChRs, ενώ οι πληροφορίες που παρέχονται από την βιβλιογραφία, σχετικά με την ετερόλογη έκφραση της α9 υπομονάδας, είναι εξαιρετικά περιορισμένες (Elgoyhen et al 2001, Verbitsky et al 2000, Filchakova and McIntosh 2013.…”
Section: έκφραση διαμεμβρανικών μορφών των α9*nachrunclassified
See 1 more Smart Citation